The role of cytology in the 21st Century: the integration of cells and molecules - Bergeron, Christine; Knebel Doeberitz, Magnus von (Acta cytologica, 2016)
Objectives: Cervical cancer screening test performance has been hampered by either a lack of sensitivity in Pap cytology or a lack of specificity of human papillomavirus (HPV) testing. This is disturbing for patients and a cause of high costs for health care providers. Study Design: The identification of p16INK4a as a specific marker for the neoplastic transformation of cervical squamous epithelial cells by HPVs allows the identification of HPV-transformed cells in cytopathology specimens. Results: When compared to molecular HPV tests for triaging minor cytologic atypia, such as atypical squamous cells of undetermined significance or low-grade squamous intraepithelial lesions, the immunochemical detection of dual p16INK4a/Ki-67-stained cells demonstrates a significantly improved specificity with good relative sensitivity. Conclusions: HPV testing has shown earlier detection of persistent high-grade squamous intraepithelial lesions (HSIL) compared to cytology and is more effective in preventing invasive cervical cancer. The next challenge for the HPV primary screening program is to find the best method(s) for selecting, among HPV-positive women, those patients in need of immediate colposcopy because they are at a higher risk of developing a precancerous lesion. An HSIL cytology result and/or dual p16/Ki-67 staining could be the best candidates, but further randomized studies are required before these approaches can be used in routine practice.
Gesehen am 07.05.2020